A biobehavioral validation of the Taylor Aggression Paradigm in female adolescents - Gaber, Lena; Parzer, Peter; Koenig, Julian; Bertsch, Katja; Brunner, Romuald; Resch, Franz; Kaess, Michael (Scientific reports, 2019)
This research assessed the behavioral, emotional, endocrinological and autonomic reactivity to the laboratory Taylor Aggression Paradigm (TAP) in a sample of healthy female adolescents. Twenty participants were induced with the TAP to behave aggressively (aggression group) and 20 age-matched participants were not induced to behave aggressively (control group). Regression analysis revealed that the aggression group displayed significant higher levels of aggressive behavior compared to the control group (χ2 (2) = 255.50, p < 0.0001). Aggressive behavior was not related to self-reported measures of trait aggression, impulsiveness or psychopathy features. Regarding the biological responses, regression analysis on cortisol, missed the set level of significance (χ2 (1) = 3.73, p = 0.054), but showed significant effects on heart rate as a function of aggression induction (χ2 (1) = 5.81, p = 0.016). While aggression induction was associated with increased autonomic arousal (heart rate), the interpretation of the effects on cortisol warrant caution, given existing differences between groups at baseline and overly elevated cortisol attributable to the general experimental procedures and not the TAP per se. No differences were found with respect to testosterone. In summary, the present study lends preliminary support for the validity of the TAP and its use in female adolescents on a behavioral and autonomic level.